(untitled) (Medicine Today, 2014)
Coronary heart disease is the most common form of heart disease and single most important cause of premature death in developed countries. It is estimated that coronary heart disease will become the major cause of death in all regions of the world by 2020. There are several modifiable risk factors of coronary heart disease. Among those diabetes mellitus is one major modifiable risk factor. So we designed this study to see the frequency of diabetes mellitus in patients with coronary heart disease in three tertiary hospitals in Bangladesh with an objective to see the frequency of diabetes mellitus in patients with coronary heart disease. This observational cross-sectional study was conducted in the department of Biochemistry of Bangabandhu Sheikh Mujib Medical University, Dhaka from July 2006 to June 2007. The study was done among 300 purposively selected diagnosed patients of coronary heart disease of both sexes. Diabetes mellitus was diagnosed according to WHO criteria. In this study we found that 23.7% of study subjects had diabetes mellitus. From this study, it can be concluded that the prevalence of diabetes (an important modifiable risk factor) is high in coronary heart disease patients. DOI: http://dx.doi.org/10.3329/medtoday.v25i2.17923 Medicine Today 2013 Vol.25(2): 67-68